2023
DOI: 10.1111/jocn.16614
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing the delivery of nutritional care by nurses for hospitalised medical patients with malnutrition; a qualitative study

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…The results showed that patients experienced the protein-enriched ice cream differently due to personal preferences of taste and texture and based on health status. As individuals have different perceptions of their needs and how they can best be met, a responsibility is placed on the nurse to help the patients to express their desires and feelings, which is described as one of the basic needs for achieving health and recovery [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The results showed that patients experienced the protein-enriched ice cream differently due to personal preferences of taste and texture and based on health status. As individuals have different perceptions of their needs and how they can best be met, a responsibility is placed on the nurse to help the patients to express their desires and feelings, which is described as one of the basic needs for achieving health and recovery [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ice cream can thus contribute to improved food intake and moreover that intake of food is perceived as more satisfactory [ 13 ]. As a nurse, it is important to see to the patient's individual needs and to help and support patients who have an insufficient nutritional intake [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When patients are empowered in awareness of malnutrition risk factors and have their role in (for example) monitoring food intake, they will be better equipped to improve their nutritional status actively. However, nurses also wonder whether it is feasible when the patient is frail or very ill ( Van Den Berg et al ). The role of the patient in hospital nutritional care and their perception about malnutrition and outcomes is hardly described in the literature ( Sladdin et al, 2017 ; Vaillancourt et al, 2014 ; Weimann et al, 2021 ).…”
Section: Review Of Literaturementioning
confidence: 99%
“…However, several studies reported that ward nurses lacked nutritional knowledge and assessment (Bollo et al, 2019; Forss et al, 2018; Noort et al, 2020; Van Den Berg et al, 2023), and seldom shared nutritional information with nurses of other facilities when older adult patients were transferred (Halvorsen et al, 2016). Hence, it is imperative to improve the practical abilities of ward nurses, such as nutritional knowledge, assessment, and sharing of nutritional information for older adult patients with other healthcare organizations.…”
Section: Introductionmentioning
confidence: 99%